2021
DOI: 10.1128/aac.01292-21
|View full text |Cite
|
Sign up to set email alerts
|

Thorough QT Study To Evaluate the Effect of Zoliflodacin, a Novel Therapeutic for Gonorrhea, on Cardiac Repolarization in Healthy Adults

Abstract: Zoliflodacin is a novel spiropyrimidinetrione antibiotic being developed as single oral dose treatment to address the growing global threat of Neisseria gonorrhoeae . To evaluate the cardiac safety of zoliflodacin, a thorough QT/QTc (TQT) study was performed in healthy subjects. In this randomized, double-blind, placebo-controlled, 4-period crossover study, 72 subjects in a fasted state received a single dose of zoliflodacin 2 g (therapeutic), zoliflodacin 4 g (supratherapeutic), placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Regarding the safety results in this phase I study, zoliflodacin doses of 3 and 4 g were well‐tolerated in both the fed and fasted states. Both the number of subjects experiencing AEs and the types of AEs were in line with the most common TEAEs reported in previous phase I and II clinical trials of zoliflodacin 18,20,21 . All reported TEAEs were mild in severity.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Regarding the safety results in this phase I study, zoliflodacin doses of 3 and 4 g were well‐tolerated in both the fed and fasted states. Both the number of subjects experiencing AEs and the types of AEs were in line with the most common TEAEs reported in previous phase I and II clinical trials of zoliflodacin 18,20,21 . All reported TEAEs were mild in severity.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, there was no notable change in QTcF values after dosing with zoliflodacin and the upper limit of the two-sided 90% CI did not exceed the regulatory threshold of 10 ms, in agreement with a TQT trial performed in a fasting state, with a 2 and 4 g dose of the granular formulation of zoliflodacin, which showed the absence of significative QT interval changes. 21 As exposure in the present study was higher in the fed state, results provided important additional data that was incorporated into a population PK model in advance of the clinical phase III study to ensure that any theoretical risk relating to QT interval changes was sufficiently minimized. Additionally, physiologically-based PK modeling efforts suggested a role for cytochrome P450 3A4 in the clearance of zoliflodacin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients should take at least 2 g of a single oral dose treatment of zoliflodacin to obtain effective N. gonorrhoeae suppression [ 136 ]. Additionally, studies revealed that the conventional therapeutic dose of 2 g does not induce cardiac arrhythmias and is well tolerated [ 137 ]. Although zoliflodacin maintains an excellent in vitro activity against clinical N. gonorrhoeae isolates, the rising potential to develop AMR led to further antibiotics research [ 138 ].…”
Section: Novel Drugs and Nano Moleculesmentioning
confidence: 99%